Genome-Wide Alteration of 5-Hydroxymethylcytosine in Hypoxic-Ischemic Neonatal Rat Model of Cerebral Palsy - Zhang, Yunpeng; Zhang, Yaodong; Chen, Danmei; Wang, Cuiting; Chen, Long; Gao, Chao; Fan, Wei; Shi, Jimin; Zhang, Jihong; Li, Bing (Frontiers in Molecular Neuroscience, 2019)
Cerebral palsy (CP)，as a neurodevelopmental disorder, usually occurs early in life and persists throughout the whole life. Several risk factors, including perinatal hypoxia-ischemia (HI), may contribute to occurrence of CP in preterm infants. DNA hydroxymethylation has been shown to play an important role in neurodevelopment and neurodegenerative disorders. However, the effect of DNA hydroxymethylation in cerebral palsy remains unknown. The aim of this study is to explore whether and how DNA hydroxymethylation is involved in cerebral palsy pathogenesis. We observed that overall 5-hydroxymethylcytosine (5hmC) abundance in the cortex of the temporal lobe of rat pups was decreased significantly after hypoxic-ischemic injury and the reduced expression of Tet1 and Tet2 enzymes might be responsible for this change. It is well-known that identified differential hydroxymethylation regions (DhMRs) are richly involved in multiple signaling pathways related to neuronal development and function. Hence, we also found that reduced 5hmC modification on the DhMRs-related genes were accompanied by the decrease of their mRNA expression levels. These results suggest that 5hmC modification is possibly involved in the pathogenesis of cerebral palsy and may potentially serve as a new therapeutic target.